1979
DOI: 10.1017/s0317167100119353
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Deficiency and Seizures in Animals and Man

Abstract: SummaryStudy of 100 children with grand mal convulsive disorders and 100 medically healthy children of matching age showed significantly lower plasma levels of vitamin E in the former (means 632.2 ± 17.3 and 822.5 ± 2\.Zßg/dl respectively; p < 0.001). This finding accords with the ability to prevent seizures in rodents by giving a-tocopherol before exposing them to a convulsion-inducing environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 2 publications
0
9
1
Order By: Relevance
“…The various neurological disorders associated with vitamin E deficiency are spinocerebellar degeneration,10, 11, 26 polyneuropathy,6, 15, 24 dysautonomia,3 myopathy,5, 23, 34 bulbar palsy,16 myoclonic dystonia,2 and seizures 22. Vitamin E deficiency has also been reported with Werdnig–Hoffmann disease30 and Bassen–Kornzweig syndrome 31.…”
Section: Discussionmentioning
confidence: 99%
“…The various neurological disorders associated with vitamin E deficiency are spinocerebellar degeneration,10, 11, 26 polyneuropathy,6, 15, 24 dysautonomia,3 myopathy,5, 23, 34 bulbar palsy,16 myoclonic dystonia,2 and seizures 22. Vitamin E deficiency has also been reported with Werdnig–Hoffmann disease30 and Bassen–Kornzweig syndrome 31.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate neurophysiological findings and Babinski’s sign suggest that both central and peripheral nerve affection contribute to the distal muscle weakness. A study comparing 100 children with generalised seizures with 100 healthy controls revealed statistically significant lower serum values of vitamin E in the epilepsy group 16. On this background, we hypothesise a possible relationship between vitamin E and epilepsy in our patient.…”
Section: Discussionmentioning
confidence: 49%
“…Vitamin E deficiency have previously been associated with seizures 13 16. A 22-year-old man with a 6-year history of epilepsy who developed spinocerebellar ataxia and sensorimotor demyelinating neuropathy had low vitamin E values 13.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E was shown to decrease the intensity of acute PTZ-sourced attacks in rats [20]. The levels of this vitamin in the blood plasma of children suffering from seizures were found to be lower than the respective values in control children of the same age [21]. Furthermore, an anti-attack effect of vitamin E was observed under experimental conditions, such as ferrous chloride model, hyperbaric oxygen model, kindling, and PTZ-evoked seizure activity [20,22,23].…”
Section: Discussionmentioning
confidence: 96%